Differences in Physical Demands and Player’s Individual Performance Between Winning and Losing Quarters on U-18 Basketball Players During Competition - Adrià Miró; Jordi Vicens-Bordas; Marco Beato; Hugo Salazar; Jordi Coma; Carles Pintado; Franc García (Journal of Functional Morphology and Kinesiology)
Background: This study examines how physical demands and individual performance influence quarter results in under-18 basketball players during a six-day basketball tournament. Methods: Twelve male players from an elite Spanish team were tracked using inertial microsensors to monitor external load variables (player load, steps, and dynamic stress load). Individual performance was assessed using the performance index rating (PIR). Results: The results showed significant differences in physical demands between quarters. Also, player load (F = 3.75, p = 0.012) and steps (F = 5.29, p = 0.001) were higher in the first quarter and decreased over time. Winning quarters had significantly higher physical demands compared to losing quarters (PL: F = 27.13, p < 0.001; steps: F = 16.70, p < 0.001; DSL: F = 9.50, p < 0.001). On the contrary, PIR did not show significant differences between winning and losing quarters (F = 2.15, p = 0.143), but tended to be higher in winning quarters. Conclusions: These results suggest that physical demands are stronger predictors of quarter results than individual performance scores, indicating that such parameters should be closely monitored by sport scientists and coaches since they can play a crucial role in team success.